A review of cyber vigilance tasks for network defense - Guidetti, Oliver Alfred; Speelman, Craig; Bouhlas, Peter (Frontiers in Neuroergonomics, 2023)
The capacity to sustain attention to virtual threat landscapes has led cyber security to emerge as a new and novel domain for vigilance research. However, unlike classic domains, such as driving and air traffic control and baggage security, very few vigilance tasks exist for the cyber security domain. Four essential challenges that must be overcome in the development of a modern, validated cyber vigilance task are extracted from this review of existent platforms that can be found in the literature. Firstly, it can be difficult for researchers to access confidential cyber security systems and personnel. Secondly, network defense is vastly more complex and difficult to emulate than classic vigilance domains such as driving. Thirdly, there exists no single, common software console in cyber security that a cyber vigilance task could be based on. Finally, the rapid pace of technological evolution in network defense correspondingly means that cyber vigilance tasks can become obsolete just as quickly. Understanding these challenges is imperative in advancing human factors research in cyber security. CCS categories Human-centered computing~Human computer interaction (HCI)~HCI design and evaluation methods.